2018
DOI: 10.1016/j.reseneeco.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the spatial and temporal determinants of gas central heating adoption

Abstract: a b s t r a c tIn order to better understand the potential for both policy and technological improvements to aid carbon abatement, long-term historical information on the time-path of transition from more traditional to cleaner fuels is useful. This is a relatively understudied element of the fuel switching literature in both developed and emerging economies. This research adds to this literature by examining the adoption time-path of network gas as a heating fuel. We merge a unique dataset on gas network roll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…As distance to the gas network increases oil is the primary alternative fuel choice with marginal probabilities of +7.1 and +13.0 percentage points. McCoy and Curtis (2018) find that a one percent increase in average distance to the Irish gas network is associated with a 12 percentage point reduction in the proportion of gas users in an area. Estimates from these two studies are not directly comparable due to differing metrics and datasets but appear broadly consistent with each other.…”
Section: 1mentioning
confidence: 88%
See 2 more Smart Citations
“…As distance to the gas network increases oil is the primary alternative fuel choice with marginal probabilities of +7.1 and +13.0 percentage points. McCoy and Curtis (2018) find that a one percent increase in average distance to the Irish gas network is associated with a 12 percentage point reduction in the proportion of gas users in an area. Estimates from these two studies are not directly comparable due to differing metrics and datasets but appear broadly consistent with each other.…”
Section: 1mentioning
confidence: 88%
“…In the case of gas, connection fees appear to be an additional barrier, as demonstrated by the estimated marginal probabilities associated with network distance of between 5 and 22 percentage points. The key price variable is the connection cost, which is a function of distance to the network (McCoy and Curtis, 2018). While the distance to the network is included in our model, we acknowledge that while projected new connections are based on a model of socio-demographic and building characteristics, income and price effects are excluded due to absence of data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…coal or peat), whereas those switching to gas, 37 per cent had previously used oil or solid fuels . Fuel switching in the context of heating system or energy efficiency retrofits can lead to substantial emission savings (Curtis et al, 2020;McCoy and Curtis, 2018). In the context of available evidence from existing energy efficiency retrofit programmes it is not possible to estimate the impact on net CO2 emissions from households.…”
Section: Changes In Home Energy Efficiency Energy Use and Emissionsmentioning
confidence: 99%
“…In addition to being a leading consumer of solid fuels, Ireland also uses a range of different solid fuels, with a substantial amount obtained from indigenous sources, specifically peat (sod peat harvested directly from bogs or manufactured peat briquettes) and wood, in addition to imported coal. Consequently, there are several research articles that have examined the determinants of solid fuel use using data from Irish households (Curtis and Pentecost, 2015; Curtis et al, 2018; Fu et al, 2014; McCoy and Curtis, 2018). Earlier studies examined the income effect and find coal and peat to be inferior goods with negative income elasticities while later studies have found strong positive effects for the proximity to a solid fuel resource, such as a peat bog, and negative effects for the presence of legislated solid-fuel sale restrictions, such as the smoky coal ban, and the availability of the gas network in the locality.…”
Section: Introductionmentioning
confidence: 99%